Perovskite solar cell based on fluorine-chlorine synergistic effect and preparation method thereof

By using 3-fluoro-4-chloroaniline iodide in the perovskite absorber layer of perovskite solar cells and using the synergistic effect of fluorochlorochlorine, the problems of low photoelectric conversion efficiency and poor stability of perovskite solar cells are solved, and more efficient photoelectric conversion and better humidity and heat stability are achieved.

CN119855352AActive Publication Date: 2025-04-18HAINAN UNIV

Patent Information

Application Number
CN202510077874.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of existing perovskite solar cells is low and have poor stability, especially in ultraviolet irradiation, high temperature and water environments, resulting in reduced performance of light emitting devices.

Method used

Using perovskite solar cells based on fluorine-chloro-synergy synergistic effects, the orderliness and stability of the film are improved by laminating structures and annealing treatment by using 3-fluoro-4-chloroaniline iodide as a modifier in the perovskite absorber layer.

Benefits of technology

The photoelectric performance of perovskite solar cells was significantly improved, the photoelectric conversion efficiency was improved, from 19.54% to 22.30%, and the initial efficiency of 86.0% was maintained at room temperature, significantly enhancing the moisture and heat stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855352A_ABST
    Figure CN119855352A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite solar cell based on a fluorine-chlorine synergistic effect. The perovskite solar cell comprises a glass substrate, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a metal electrode which are sequentially stacked, wherein the perovskite light absorption layer is obtained by coating and annealing a perovskite precursor solution containing 3-fluoro-4-chloroaniline iodide. According to the invention, the 2D / 3D perovskite thin film processed by the 3-F-4-ClAnI shows a highly ordered crystal structure, and the photoelectric property of the 2D / 3D perovskite solar cell is obviously improved; and the optimal Pb-I-Pb torsion angle is optimized through the synergistic effect of C-F and C-Cl groups, and the coordination effect of Pb < 2 + > is remarkably enhanced. Compared with the unmodified FAPbI3, the stability of the perovskite thin film device processed by the 3-F-4-ClAnI is obviously enhanced, the non-radiative recombination is effectively inhibited, the interface charge extraction is improved, and the perovskite thin film device has excellent long-term stability at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solar cell preparation, and in particular to a perovskite solar cell based on the synergistic effect of fluorine and chlorine and a preparation method thereof. Background Art

[0002] Organic-inorganic hybrid perovskites (OIHPSs) are star semiconductor materials with significant advantages in next-generation photovoltaic devices. Due to their excellent properties such as suitable band gap, high carrier mobility and strong light absorption coefficient, they have become the most promising candidates for photovoltaic devices. However, the use of organic cations (such as CH3NH 3+ 、CH(NH2) 2+ , Cs + ) are difficult to cope with the serious non-radiative effects caused by deep defects, which results in very poor environmental stability of traditional three-dimensional perovskite materials. They are easily decomposed under ultraviolet irradiation, high temperature and water environment, which leads to a significant reduction in the performance of light-emitting devices.

[0003] In recent years, two-dimensional perovskites as passivators have been proven to be a potential strategy to improve the wet-heat stability and photoelectric performance of perovskite solar cells, among which organic ammonium salts containing F or Cl are widely used. For example, CN202210534746.5 discloses a carbon-based inorganic perovskite solar cell passivated with ammonium fluoride salt and a preparation method thereof, which effectively passivates the surface defects of the inorganic perovskite light-absorbing layer with ammonium fluoride salt, optimizes the arrangement of the interface energy levels, and significantly improves the hydrophobicity of the inorganic perovskite light-absorbing layer while suppressing the non-radiative recombination of charges, ultimately improving the efficiency and humidity stability of the device. Although the strong electronegativity of fluorine atoms can absorb electrons and form -NH 3+ The side induces more positive charge accumulation, but the change in the position of fluorine also changes the electron density distribution on the benzene ring. Chinese patent CN202211487944.7 discloses a method for efficiently passivating a lead iodide-rich wide-bandgap perovskite with pure chlorine two-dimensional perovskite and its solar cell. Although Cl ions can be easily incorporated into the perovskite lattice, they have stronger Pb-Cl bonds and provide effective passivation, thereby reducing photovoltaic properties. However, due to the limited passivation effect of the chlorine element and the electron cloud density around the halogen atoms, they also affect each other. Therefore, the photoelectric conversion efficiency of existing perovskite solar cells is limited, and it is necessary to develop a perovskite solar cell with a more efficient photoelectric conversion efficiency and a preparation method thereof, which is of great significance for promoting the preparation of efficient and stable perovskite solar cells. Summary of the invention

[0004] In view of this, the present invention provides a perovskite solar cell to solve the problems of low photoelectric conversion efficiency and poor stability of existing perovskite solar cells.

[0005] On the one hand, the present invention adopts a perovskite solar cell based on the synergistic effect of fluorine and chlorine, comprising a glass substrate, an electron transport layer, a perovskite light-absorbing layer, a hole transport layer and a metal electrode stacked in sequence, wherein the perovskite light-absorbing layer is obtained by coating and annealing a perovskite precursor solution containing 3-fluoro-4-chloroaniline iodide.

[0006] Preferably, the amount of 3-fluoro-4-chloroaniline iodide used is 2.7-5.5 mg.

[0007] Another aspect of the present invention is a method for preparing a perovskite solar cell based on the synergistic effect of fluorine and chlorine, comprising the following steps:

[0008] (1) Preparation of glass substrate: A FTO glass substrate was cleaned with detergent, deionized water, acetone and isopropanol in sequence, then dried and treated with ozone;

[0009] (2) Preparation of electron transport layer: SnO2 colloidal precursor is coated on FTO glass substrate and annealed;

[0010] (3) Preparation of perovskite light absorbing layer: spin coating a perovskite precursor solution containing 3-fluoro-4-chloroaniline iodide on the electron transport layer and annealing;

[0011] (4) Preparation of hole transport layer: A solution of 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene is deposited on the perovskite light absorbing layer to obtain a hole transport layer.

[0012] (5) Preparation of metal electrodes: Au electrodes are obtained by thermal evaporation in a vacuum chamber using a mask, and finally a perovskite solar cell based on the synergistic effect of fluorine and chlorine is obtained.

[0013] Preferably, in step (3), 548.6 mg of lead iodide, 77.07 mg of lead bromide, 190.12 mg of potassium iodide ether, 21.84 mg of methylammonium bromide and 4.2 mg of 3-F-4-ClAnI are dissolved in a DMF / DMSO mixed solvent, and then 34 μL of a CsI stock solution with a concentration of 519 mg / mL is added and stirred to prepare a perovskite precursor solution, and then 80 uL of the perovskite precursor solution is deposited on the SnO2 film at a speed of 2000 rpm for 10 s, and then deposited at a speed of 6000 rpm for 45 s. 15 s before the end of the second spin coating, 0.2 mL of chlorobenzene is added dropwise to the spin substrate, and then annealed at 110° C. for 60 min to obtain a perovskite light absorbing layer.

[0014] Preferably, in step (3), 1202 mg of formamidine lead triiodide, 33.76 mg of methylammonium chloride, 4.2 mg of 3-F-4-ClAnI and 8.21 mg of methylamine lead bromide are weighed and dissolved in 1 mL of a mixed solvent of DMF and DMSO to prepare a perovskite precursor solution, 80 uL of the perovskite precursor solution is coated on the prepared SnO2 substrate at a speed of 5500 rpm, 0.12 mL of ether is dropped as an anti-solvent during the spin coating process, and then annealed at a temperature of 150° C., and 4 mg / mL of octylamine iodide is spin-coated on the perovskite film to obtain.

[0015] Preferably, in step (3), the concentration of 3-F-4-ClAnI in the perovskite precursor solution is 0.1-0.2 mol / mL.

[0016] Preferably, in step (4), the 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene solution further comprises a lithium bis(trifluoromethanesulfonyl)imide stock solution, tributyl phosphate and chlorobenzene.

[0017] By adopting a preparation method of a perovskite solar cell based on fluorine-chlorine synergistic effect provided by the present invention, the perovskite light-absorbing layer is treated with 3-fluoro-4-chloroaniline iodide, and it is found that the 2D / 3D perovskite film treated with 3-F-4-ClAnI not only exhibits the highest ordered crystal structure, but also significantly improves the photoelectric performance of the 2D / 3D perovskite solar cell (from 19.54% to 22.30%; from 23.27% to 24.74%); and the synergistic effect of CF and C-Cl groups optimizes the optimal Pb-I-Pb torsion angle, while the synergistic effect between F and Cl atoms significantly enhances the Pb 2+ Compared with the unmodified FAPbI3, the stability of the perovskite cell modified with 3-F-4-ClAnI was significantly enhanced, its non-radiative recombination was effectively suppressed, the interfacial charge extraction was improved, and it had excellent long-term stability at room temperature (maintaining 86.0% of the initial efficiency after 700h of maximum power point tracking). BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the formation of perovskite solar film modified by 3-F-4-ClAnI;

[0019] Figure 2 PL intensity diagrams of the front and back surfaces of the FA / MA (n=2) perovskite single crystal and the perovskite film of Example 1;

[0020] Figure 3 The electron microscope scanning test images of the perovskite films prepared in Example 1 and Comparative Example 1;

[0021] Figure 4 The humidity stability test of the unpackaged perovskite cell under environmental conditions (RH: 50±10%, 25° C.) of Example 1 and Comparative Example 1, wherein Control represents Comparative Example 1 and Target represents Example 1;

[0022] Figure 5 Steady-state PL intensity diagram of perovskite films modified with 3-F-4-ClAnI at different concentrations;

[0023] Figure 6 JV curves of the 3-F-4-ClAnI modified FAPbI3 device prepared in Example 2 and the standard FAPbI3 prepared in Comparative Example 3.

[0024] Figure 7 This is a stability test chart of the standard sample device prepared in Comparative Example 1 and the 3-F-4-ClAnI modified device prepared in Example 1 operated at 35 degrees Celsius for 700 hours. DETAILED DESCRIPTION

[0025] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0026] 3-Fluoro-4-chloroaniline iodide (3-F-4-ClAnI), 3-chloro-4-fluoroaniline iodide (3-Cl-4-FAnI), 3,4-dichloroaniline iodide (34-ClAnI) and 3,4-difluoroaniline iodide (3,4-FAnI) can be purchased or prepared according to existing methods.

[0027] Example 1: A perovskite solar cell based on the synergistic effect of fluorine and chlorine, comprising a glass substrate, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a metal electrode stacked in sequence. The specific preparation method comprises the following steps:

[0028] (1) Preparation of glass substrate: The FTO glass substrate was cleaned with detergent, deionized water, acetone and isopropanol for 15 minutes in sequence, then dried and treated with UV ozone for 20 minutes before use;

[0029] (2) Preparation of electron transport layer: 80uL of diluted SnO2 colloidal precursor (15% SnO2 by mass and a volume ratio of 1:3 with water) was spin-coated on a cleaned FTO glass substrate at 4000rpm for 30s, and then annealed on a hot plate at 150°C for 30min.

[0030] (3) Preparation of perovskite light absorbing layer: The perovskite light absorbing layer was deposited in a glove box filled with N2. 548.6 mg of lead iodide, 77.07 mg of lead bromide, 190.12 mg of potassium iodide ether, 21.84 mg of methylammonium bromide and 4.2 mg of 3-F-4-ClAnI were weighed and dissolved in 1 mL of DMF / DMSO (v / v=4:1) mixed solvent, and then 34 μL of CsI stock solution (519 mg of CsI dissolved in 1 mL of DMSO) was added and stirred for 2 h to prepare the perovskite precursor solution. Then 80 uL of the perovskite precursor solution was deposited on the SnO2 film at a speed of 2000 rpm for 10 s, and then at a speed of 6000 rpm for 45 s. 15 s before the end of the second spin coating, 0.2 mL of anti-solvent chlorobenzene was added dropwise on the spin substrate, and then annealed at 110 °C for 60 min to obtain Cs 0.05 MA 0.16 FA 0.79 Pb(I 0.83 Br 0.17 )3 Perovskite material (crystal growth diagram as shown Figure 1 , indicating that it formed 2D / 3D perovskite crystals), where the concentration of 3-F-4-ClAnI in the perovskite precursor solution was 0.15 mol / mL.

[0031] (4) Preparation of hole transport layer: 72.3 mg of 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), 35 μL of lithium bis(trifluoromethanesulfonyl)imide stock solution (260 mg of Li-TFSI added to 1 mL of acetonitrile), 30 μL of tributyl phosphate (t-BP) and 1 mL of chlorobenzene were prepared into a spin coating solution, and 80 μL of the spin coating solution was deposited on the prepared perovskite light absorbing layer at a rotation speed of 3000 rpm for 30 s.

[0032] (5) Metal electrode preparation: Use a mask to prepare a metal electrode in a vacuum chamber (1×10 -4 The Au electrode with a thickness of 100 nm was obtained by thermal evaporation in 1000 μm Pa. The preparation of (2), (3) and (4)) above was all carried out in a coater.

[0033] Example 2: The difference between Example 2 and Example 1 is that the preparation of the perovskite light-absorbing layer is different: 1202 mg of formamidinium lead triiodide and 33.76 mg of methylammonium chloride, 4.2 mg of 3-F-4-ClAnI and 8.21 mg of methylammonium lead bromide were weighed and dissolved in 1 mL of a mixed solvent of DMF and DMSO (v / v=4:1) to prepare a perovskite precursor solution, and 80 uL of the perovskite precursor solution was coated on the prepared SnO2 substrate at a speed of 5500 rpm for 50 s, and 0.12 mL of ether was dropped as an anti-solvent 13 s before the end of the spin coating, and then annealed at a temperature of 150°C for 15 min, and then 4 mg / mL of octyl ammonium iodide (isopropanol as solvent) was spin-coated on the perovskite film at a speed of 3000 rpm for 30 s.

[0034] Examples 3 to 5: The difference between Examples 3 to 5 and Example 1 is that the addition amount of 3-F-4-ClAnI single crystal in step (3) is 1.4 mg, 2.7 mg and 5.5 mg, and the concentration of 3-F-4-ClAnI in the perovskite precursor solution is 0.05 mg / mL, 0.10 mg / mL and 0.20 mg / mL, respectively.

[0035] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that 3-F-4-ClAnI is not added in step (3).

[0036] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that 3-chloro-4-fluoroaniline iodide (3-Cl-4-FAnI), 3,4-dichloroaniline iodide (3,4-ClAnI) and 3,4-difluoroaniline iodide (3,4-FAnI) are used to replace 3-fluoro-4-chloroaniline iodide (3-F-4-ClAnI). The JV curves of the prepared devices of the perovskite solar cells prepared in Example 1 and Comparative Example 1 are tested. As shown in the results in Table 1, the perovskite light-absorbing layer is modified by 3-F-4-ClAnI, and the synergistic effect of CF and C-Cl groups significantly enhances the Pb 2+ The coordination effect achieved a higher photoelectric conversion efficiency (increased from 19.54% to 22.30%).

[0037] Table 1: Comparison of photoelectric conversion efficiency of perovskite solar cells prepared in Example 1, Comparative Example 1 and Comparative Example 2

[0038]

[0039] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that 3-F-4-ClAnI is not added in step (3), and the other steps are the same.

[0040] The performance of the perovskite solar cells prepared in Examples 1 to 5 and Comparative Examples 1 to 2 was tested, and the results are as follows:

[0041] (1) Steady-state PL spectra of FA-based (n=2, 3-F-4ClAn2FAPb2I7) and MA-based (n=2, 3-F-4ClAn2MAPb2I7) 2D perovskite single crystals prepared with 3-F-4ClAnI salt, and steady-state PL spectra of 2D / 3D perovskite films treated with 3-F-4-ClAnI excited on the front and back sides of glass at the beginning of thermal annealing, as shown in Figure 2. Figure 2 As shown, it can be inferred that the FA-based 2D template with n = 2 is first formed at the air / liquid interface and immediately serves as a skeleton to template the epitaxial growth of the 3D perovskite film, indicating a top-down preferential growth direction to form a 2D / 3D perovskite film.

[0042] (2) The perovskite films prepared in Example 1 and Comparative Example 1 were subjected to electron microscope scanning tests. Figure 3 The SEM images show that compared with the perovskite film of comparative example 1, which shows highly disordered film quality, residual PbI2 and small grain size (300nm), the cross-sectional scanning electron microscope (SEM) image of example 1 shows the overall particles (400nm) from top to bottom, without obvious gaps, and the well-stacked vertical perovskite particles can transport carriers without crossing the grain boundary (GB), thereby promoting carrier migration and suppressing non-radiative recombination. It shows that the 2D / 3D perovskite film treated with 3-F-4-ClAnI exhibits the highest ordered crystal structure, significantly improving the photoelectric performance of 2D / 3D perovskite solar cells (PSCs).

[0043] (3) The humidity stability test of the unencapsulated perovskite battery under environmental conditions (RH: 50±10%, 25°C) was conducted on Example 1 and Comparative Example 1, where Control represents Comparative Example 1 and Target represents Example 1. The results are shown in FIG. Figure 4 As shown. After exposure to a dark environment with high humidity (RH = 50 ± 10%, T = 25 ° C) for 1000h, the PCE retention rate of Example 1 is 91.6%, while the PCE retention rate of Comparative Example 1 is only 51.2%. Therefore, compared with the unmodified FAPbI3, the stability of the 3-F-4-ClAnI perovskite device is significantly enhanced, the non-radiative recombination is effectively suppressed, the interface charge extraction is improved, and it can be preserved for a long time in the environment, which has potential application prospects.

[0044] (4) Steady-state PL intensity diagrams of 3-F-4-ClAnI modified perovskite films prepared in Example 1 and Examples 3 to 5, respectively, are shown in FIG. Figure 5The results show that the 3-F-4-ClAnI modified perovskite film prepared in Example 1 has a more obvious blue shift and the highest PL intensity, indicating that the perovskite film prepared in Example 1 has the lowest defect density and the best film quality.

[0045] (5) The standard FAPbI3 prepared in Comparative Example 3 and the 3-F-4-ClAnI modified FAPbI3 device prepared in Example 2 were tested, and the JV curves thereof are shown in FIG. Figure 6 The results show that, using a coating method and raw materials different from those in Example 1, the photoelectric conversion efficiency of the perovskite film modified with 3-F-4-ClAnI is significantly improved compared with the original standard sample (from 23.27% to 24.74%), indicating that the perovskite film modified with 3-F-4-ClAnI is also suitable for different experimental schemes. It also indirectly verifies that under the modification of 3-F-4-ClAnI, the Pb-I-Pb torsion angle of the perovskite film is optimal, and the fluorine / chlorine substituted 3,4-An + and uncoordinated Pb 2+ Pb 2+ Halide interactions also play an important role in enhancing the stability of 2D / 3D perovskites.

[0046] (6) Testing the stability of the perovskite solar cell devices prepared in Example 1 and Comparative Example 1

[0047] like Figure 7 As shown, the devices of the standard sample of comparative example 1 and embodiment 1 modified with 3-F-4-ClAnI maintained 40.3% and 86.0% of the initial efficiency respectively after 700 hours of maximum power point tracking under 35° continuous illumination, indicating that the molecule forms a stable 2D / 3D perovskite film and improves the stability of the overall device.

[0048] In summary, the preparation method of perovskite solar cells based on fluorine-chlorine synergistic effect provided by the present invention is adopted, and the perovskite light-absorbing layer is modified by 3-fluoro-4-chloroaniline iodide. It is found that the 2D / 3D perovskite film treated with 3-F-4-ClAnI not only exhibits the highest ordered crystal structure, but also significantly improves the photoelectric performance of 2D / 3D perovskite solar cells (PSCs); and the synergistic effect of CF and C-Cl groups optimizes the optimal Pb-I-Pb torsion angle, while the synergistic effect between F and Cl atoms significantly enhances the Pb 2+ Compared with the unmodified FAPbI3, the stability of the 3-F-4-ClAnI perovskite film is significantly enhanced, the non-radiative recombination is effectively suppressed, the interfacial charge extraction is improved, and it has excellent long-term stability at both room temperature and high temperature.

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A perovskite solar cell based on the synergistic effect of fluorine and chlorine, comprising a glass substrate, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a metal electrode stacked in sequence, characterized in that: The perovskite light-absorbing layer is obtained by coating a perovskite precursor solution containing 3-fluoro-4-chloroaniline iodide and annealing.

2. A perovskite solar cell based on fluorine-chlorine synergy according to claim 1, characterized in that: The dosage of the 3-fluoro-4-chloroaniline iodide is 2.7-5.5 mg.

3. A method for preparing a perovskite solar cell based on the synergistic effect of fluorine and chlorine, characterized in that: The following steps are involved: (1) Preparation of glass substrate: A FTO glass substrate was cleaned with detergent, deionized water, acetone and isopropanol in sequence, then dried and treated with ozone; (2) Preparation of electron transport layer: SnO2 colloidal precursor is coated on FTO glass substrate and annealed; (3) Preparation of perovskite light absorbing layer: spin-coat a perovskite precursor solution containing 3-fluoro-4-chloroaniline iodide on the electron transport layer and anneal to obtain a SnO2 thin film; (4) Preparation of hole transport layer: A solution of 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene is deposited on the perovskite light absorbing layer to obtain a hole transport layer. (5) Preparation of metal electrodes: Au electrodes are obtained by thermal evaporation in a vacuum chamber using a mask, and finally a perovskite solar cell based on the synergistic effect of fluorine and chlorine is obtained.

4. The method for preparing a perovskite solar cell based on fluorine-chlorine synergy according to claim 3, characterized in that: In the step (3), 548.6 mg of lead iodide, 77.07 mg of lead bromide, 190.12 mg of potassium iodide ether, 21.84 mg of methylammonium bromide and 4.2 mg of 3-F-4-ClAnI were dissolved in a DMF / DMSO mixed solvent, and then 34 μL of a CsI stock solution with a concentration of 519 mg / mL was added and stirred to prepare a perovskite precursor solution. Then 80 uL of the perovskite precursor solution was deposited on the SnO2 film at a speed of 2000 rpm for 10 s, and then deposited at a speed of 6000 rpm for 45 s. 15 s before the end of the second spin coating, 0.20 mL of chlorobenzene was dropped on the spin substrate, and then annealed at 110° C. for 60 min to obtain a perovskite light absorbing layer.

5. The method for preparing a perovskite solar cell based on fluorine-chlorine synergy according to claim 3, characterized in that: In the step (3), 1202 mg of formamidine lead triiodide, 33.76 mg of methylammonium chloride, 4.2 mg of 3-F-4-ClAnI and 8.21 mg of methylamine lead bromide are weighed and dissolved in 1 mL of a mixed solvent of DMF and DMSO to prepare a perovskite precursor solution, 80 uL of the perovskite precursor solution is coated on the prepared SnO2 film at a speed of 5500 rpm, and the coating is performed twice in succession. After the coating, 0.12 mL of ether is dropped as an anti-solvent, and then annealed at a temperature of 150° C., and 4 mg / mL of octylamine iodide is spin-coated on the perovskite film to obtain a film.

6. The method for preparing a perovskite solar cell based on fluorine-chlorine synergy according to claim 3, characterized in that: In the step (3), the concentration of 3-F-4-ClAnI in the perovskite precursor solution is 0.1-0.2 mol / mL.

7. The method for preparing a perovskite solar cell based on fluorine-chlorine synergy according to claim 4, characterized in that: In the step (4), the 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene solution further comprises a lithium bis(trifluoromethanesulfonyl)imide stock solution, tributyl phosphate and chlorobenzene.

Citation Information

Patent Citations

  • Efficient perovskite solar cell and preparation method thereof

    CN113363390A

  • Preparation method of perovskite solar cell with hole extraction type heterostructure

    CN115802856A

  • Synergistic passivation perovskite solar cell and preparation method thereof

    CN118450730A

  • Bulk phase passivation perovskite light absorption layer, solar cell and preparation method

    CN119300617A

Cited By

  • Perovskite thin film and preparation method and application thereof

    CN121510844A

  • Perovskite thin film and preparation method and application thereof

    CN121510844B